2019
DOI: 10.12659/msm.918288
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Role of Expression of Nectin-4 in Esophageal Cancer

Abstract: Background:Nectin-4 is overexpressed in several human malignant tumors. This study aimed to investigate the expression of Nectin-4 in esophageal cancer tissues compared with adjacent normal esophageal tissue and its association with clinicopathological parameters and prognosis. Material/Methods:Nectin-4 expression in esophageal cancer tissues was compared with adjacent normal esophageal tissue from 94 patients using immunohistochemistry, Western blot, and quantitative reverse transcription-polymerase chain rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 18 publications
2
20
0
Order By: Relevance
“…It also has a key role in modulating cellular viability and movement capacity [13][14][15][16]. Importantly, an increasing number of studies have demonstrated that Nectin-4 is specifically overexpressed in various cancers [20][21][22]. For example, Challita-Eid et al [35] collected more than two thousand tumor samples containing head/neck, lung, bladder, breast, pancreatic, ovarian, and esophageal tumors; in two-thirds of all specimens obviously high expression of Nectin-4 was detected by IHC staining.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It also has a key role in modulating cellular viability and movement capacity [13][14][15][16]. Importantly, an increasing number of studies have demonstrated that Nectin-4 is specifically overexpressed in various cancers [20][21][22]. For example, Challita-Eid et al [35] collected more than two thousand tumor samples containing head/neck, lung, bladder, breast, pancreatic, ovarian, and esophageal tumors; in two-thirds of all specimens obviously high expression of Nectin-4 was detected by IHC staining.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Challita-Eid et al [35] collected more than two thousand tumor samples containing head/neck, lung, bladder, breast, pancreatic, ovarian, and esophageal tumors; in two-thirds of all specimens obviously high expression of Nectin-4 was detected by IHC staining. Moreover, a large number of studies demonstrated that overexpression of Nectin-4 served as a tumor-associated inducer in various malignant tumors, including colorectal, lung, pancreatic, ovarian, and breast cancers [18][19][20][21][22][23]. Until now, little is known about whether or not Nectin-4 exerts a vital influence on OS oncogenesis and development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nectin-4 has been identified as a prognostic marker in different cancers such as esophageal, lung, breast and pancreatic cancer [17,18,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%